Stochastic resonance in MoS2 photodetector - Akhil Dodda (Nature Portfolio, 2020)
Here, the authors take advantage of stochastic resonance in a photodetector based on monolayer MoS2 for measuring otherwise undetectable, ultra-low-intensity, subthreshold optical signals from a distant light emitting diode in the presence of a finite and optimum amount of white Gaussian noise.